Engelhardt on the Common Morality in Bioethics - Iltis, Ana S. (Conatus - Journal of Philosophy, 2018)
Contemporary bioethics is, at least in part, the product of biomedical and sociopolitical changes in the middle to latter part of the 20th century. These changes prompted reflection on deep moral questions at a time when traditional sources of moral guidance no longer were widely respected and, in some cases, were being rejected. In light of this, scholars, policy makers, and clinicians sought to identify a common morality that could be used among persons with different moral commitments to resolve disputes and guide clinical practice and health policy. The concept of the common morality remains important in bioethics. This essay considers the common morality in light of the work of H. Tristram Engelhardt, Jr.